1992
DOI: 10.1093/ajcp/97.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of p53 Expression in Microwave-Fixed, Paraffin-Embedded Sections of Colorectal Carcinoma and Adenoma

Abstract: Expression of p53, a tumor-suppressor gene product, was studied immunohistochemically in microwave-fixed, paraffin-embedded sections of 84 colorectal carcinomas and 44 adenomas. Using a monoclonal antibody (PAb1801), nuclear p53 was detected successfully in 51 of 84 (60.7%) cases of carcinomas, and no stain for p53 was demonstrated in the adjacent normal mucosa. The results in the microwave-fixed, paraffin-embedded sections correlated with those in the frozen sections. The incidence of p53 expression in colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…More than 50% of adenomas containing cancer (35) and 37% to 70% of cancers (19,26,37,39,40,45,53,56,(69)(70)(71)(72) have been found to have p53 overexpression. Interpretation of p53 immunohistochemistry is a common difficulty in generalizing studies and although the correlation with p53 mutation is far from perfect, p53 overexpression has been used as a surrogate for mutation in numerous studies (15, 19, 39, 40, 53, 55, 56, 68, 71).…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of adenomas containing cancer (35) and 37% to 70% of cancers (19,26,37,39,40,45,53,56,(69)(70)(71)(72) have been found to have p53 overexpression. Interpretation of p53 immunohistochemistry is a common difficulty in generalizing studies and although the correlation with p53 mutation is far from perfect, p53 overexpression has been used as a surrogate for mutation in numerous studies (15, 19, 39, 40, 53, 55, 56, 68, 71).…”
Section: Discussionmentioning
confidence: 99%
“…Of these genes, it is clear that p53 is involved in both cell cycle and apoptosis regulation; the p53 gene appears to be inactivated in up to 60% of colorectal carcinomas [4]. It has been shown that the p53 protein can cause cell cycle arrest but can also stimulate apoptosis, and the hypothesis currently favoured is that genomic damage leads to up-regulation of p53 expression, which halts the cell cycle to allow DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Altered p53 tumor suppressor gene is currently recognized as the most common gene aberration in human malignancy, 3,6,7,[11][12][13]15,16,23,27,29 with important prognostic and diagnostic properties. This study was undertaken to investigate the value of p53 protein immunostain in the identification of carcinoma cells in pleural and peritoneal fluids.…”
Section: Resultsmentioning
confidence: 99%
“…2,10,20,21 Mutation of p53 tumor suppressor gene is currently believed to be the most common genetic alteration in human malignancy. 3,7,12,13,15,16,23,27 The mutant gene can be assessed indirectly by immunohistochemical staining because the aberrant gene produces abnormal p53 protein with a long half-life that accumulates to a detectable level in cell nuclei. 3,6,23,27 Studies have shown a good correlation between the altered gene and the measurement of p53 protein by immunohistochemistry on formalinfixed, paraffin-embedded tissue sections.…”
Section: Discussionmentioning
confidence: 99%